Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1086/587789
|View full text |Cite
|
Sign up to set email alerts
|

Geological Structure of an Arsenic‐Contaminated Aquifer at Sonargaon, Bangladesh

Abstract: Continuous sediment core samples and groundwater were collected in the northern part of Sonargaon, central Bangladesh, to document the hydrogeological constraints on As-contaminated aquifers. The study area spans the alluvial plain of the Old Brahmaputra River and a Pleistocene terrace, the Madhupur Tract. The Quaternary sequence comprises Plio-Pleistocene sand, Upper Pleistocene mud, and Holocene sand units. HighlyAs-contaminated groundwater ( 50 -1000 μg/L) is found in the upper aquifer corresponding to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 20 publications
2
17
1
Order By: Relevance
“…1a), the depth at which most wells extract water 7 . A similar arsenic pattern has been observed at other sites 1,3,4,[8][9][10] and regionally 1 (see Supplementary Information). Previous research at our site provides some insight into the source of the contaminated water.…”
supporting
confidence: 83%
“…1a), the depth at which most wells extract water 7 . A similar arsenic pattern has been observed at other sites 1,3,4,[8][9][10] and regionally 1 (see Supplementary Information). Previous research at our site provides some insight into the source of the contaminated water.…”
supporting
confidence: 83%
“…Arsenic content ranged from non-detectable to 36.87 mg/kg, with the average value of 5.6 mg/kg. Core samples collected adjacent to a highly As contaminated tube well show that high As concentrations (from 7.0 to 36.87 mg/kg) are found down to 44.5 m, with the highest content at 44.5 m. Below that, the sediments are mainly medium to coarse sand, and As concentrations decrease abruptly down to stable low concentrations It is, therefore, postulated that the vertical leakage and translocation, controlled by electrical conductivity, dissolved organic matter, and land gradient, play a key role in the distribution of As from the upper aquifer to the middle one [35,41]. The present study and previous studies in Bangladesh and West Bengal, India, have shown that the source(s) of As seems to be locally distributed in lenses of fine-grained sediments (e.g., silty sand, clayey silt, clay), and peat in the Holocene deposits of the upper aquifer, which contain also high concentrations of Fe, Mn and Al oxides and organic matter [14,33,[42][43][44].…”
Section: Sediment Characteristicsmentioning
confidence: 99%
“…Seddique et al [33], Itai et al [34] and Mitamura et al [35] speculated that reduction of Fe oxyhydroxide is not the only mechanism of As mobilization. In addition, chemical weathering of biotite and/or other basic minerals induced by infiltration of oxic surface water in the Holocene aquifer could be important as a primary cause of As mobilization, because the biotite minerals contained high As concentrations.…”
Section: Scanning Electron Microscope (Sem)mentioning
confidence: 99%
See 2 more Smart Citations